A Visualized Dynamic Prediction Model for Overall Survival in Elderly Patients With Pancreatic Cancer for Smart Medical Services - Zhong, Jiang; Liao, XingShu; Peng, Shuang; Cao, Junyi; Liu, Yue; Liu, Chunyang; Qiu, Ju; Guan, Xiaoyan; Zhang, Yang; Liu, Xiaozhu; Peng, Shengxian (Frontiers in Public Health, 2022)
Abstract Background: Pancreatic cancer （PC）is a highly malignant tumor of the digestive system,The number of elderly patients with PC is increasing, and older age is related to a worse prognosis. Accurate prognostication is crucial in treatment decisions made for people diagnosed with PC. However, an accurate predictive model for the prognosis of these patients is still lacking. We aimed to construct nomograms for predicting the overall survival(OS) of Elderly patients with PC. Methods: PC patients older than 65 years old from 2010 to 2015 in the Surveillance, Epidemiology and End Results (SEER) database were selected and randomly divided into training cohort（n=4586） and validation cohort（n=1966）. Patients’ data in 2016-2018 (n = 1761) was used for external validation.Univariable and forward stepwise multivariable Cox analysis was used to determine the independent prognostic factors. Overall Survival (OS) was determined using Kaplan–Meier survival curves. We used significant variables in the training set to construct nomograms predicting prognosis. The performance of the models was evaluated for their discrimination and calibration power based on the concordance index (C-index) , calibration curve, and the decision curve analysis (DCA). Results: Age, Insurance, Grade, Surgery, Radiation, Chemotherapy, T, N, and AJCC were independent predictors for OS and thus were included in our nomogram. In the training cohort and validation cohort, the concordance indices(C-indices) of our nomogram were 0.725（95%CI：0.715-0.735）and 0.711（95%CI：0.695-0.727）, respectively. The 1-, 3-, and 5-year areas under receiver operating characteristic curves (AUCs) showed similar results. The calibration curves showed a high consensus between observations and predictions. In the external validation cohort, C-index(0.797, 95%CI: 0.778–0.816) and calibration curves also revealed high consistency between observations and predictions. The nomogram-related decision curve analysis (DCA) curves showed better clinical utility compared to TNM staging. In addition, we have developed an online prediction tool for OS. Conclusions: A web-based prediction model for OS in elderly PC patients was constructed and validated, which may be useful for prognostic assessment, treatment strategy selection, and follow-up management of these patients.